Circulating miRNAs as Potential Alternative Cell Signaling Associated with Maternal Recognition of Pregnancy in the Mare. Issue 6 (1st December 2016) - Klohonatz, Kristin M.; Cameron, Ashely D.; Hergenreder, Joanna R.; da Silveira, Juliano C.; Belk, Aeriel D.; Veeramachaneni, D.N.R.; Bouma, Gerrit J.; Bruemmer, Jason E.
Abstract: During early pregnancy, the conceptus and mare communicate to establish pregnancy. Cell-secreted vesicles (e.g., exosomes) have been reported in serum. Exosomes contain bioactive materials, such as miRNA, that can mediate cell responses. We hypothesized that a) exosomes are present in mare circulation and quantity varies with pregnancy status, b) exosomes contain miRNAs unique to pregnancy status, and c) miRNAs target pathways in endometrium based upon pregnancy status of the mare. First, serum samples were obtained from mares in a crossover design, with each mare providing samples from a pregnant and nonmated control cycle (n = 3/sample day) on Days 12, 14, 16, and 18 postovulation. Flow cytometry revealed the presence of serum microvesicles in mares in two different-sized populations (greater than or less than 100 nm), validated by transmission electron microscopy. Second, serum was collected on Days 9, 11, and 13 (n = 4/day), and endometrial biopsies were collected on Days 11 and 13 (n = 3/day) from pregnant and nonmated mares. Total RNA from serum exosomes was evaluated with quantitative RT-PCR using equine-specific miRNA sequences. A total of 12 miRNAs were found in different quantities on the specified days. Pathway analysis suggested that miRNAs targeted focal adhesion molecules (FAMs). Transcripts corresponding to FAMs were evaluated in endometrial biopsies. Protein levels and localization for PAK6 and RAF1 were further evaluated. Our data suggest that serum exosomes contain miRNA that differ based upon pregnancy status, and may affect mRNA expression related to focal adhesion pathway in the endometrium, with a potential role in maternal recognition of pregnancy.